Feminist spiritualities, gender equality and sustainable development: The possibilities of a countermovement - N. Swanepoel; T. van Wyk (Acta Theologica)
Feminist historiography indicates that spirituality has historically been one of the instruments whereby women could “speak”. This “voice” implied recognition and authority, to a certain degree, in a patriarchal-oriented reality. In this regard, feminist spirituality became a vehicle for women to authorise their own religious and spiritual contributions and insights. Feminist spirituality became a countermovement – countering perceptions and ingrained convictions that a woman could not be a mediator between God and humanity. Feminist spirituality contributed to the creation of spaces for women to study and participate in the creation of religious-spiritual texts. Women’s contexts are diverse and intersectional, and so is feminist spirituality, to the extent that it is more appropriate to speak of feminist spiritualities in the plural. This article explores the possibilities of feminist spirituality as countermovement that contributes to the realisation of gender equality, in the way that gender equality finds expression in the Sustainable Development Goals of the United Nations. It is situated within a growing field of work that explores how faith communities’ religion and spirituality contribute to their being agents of sustainable development, and within the contextual urgency of the sustainable development agenda.